Integrated water resources management under uncertainty: exploring interconnected technological, infrastructural and institutional solutions - Wostoupal, Benjamin, author; Arabi, Mazdak, advisor; Goemans, Christopher, committee member; Dozier, André, committee member (Colorado State University. Libraries, 2018)
Rapidly growing populations in many of the world's semiarid regions intensify competition for increasingly scarce freshwater resources. Growing urban demands, land-use change, and a changing climate will further exacerbate regional vulnerability to water scarcity. The intensification of these trends creates several challenges for the future planning and management of water resources. In this work we employ the use of an integrated socioeconomic, hydrologic, and ecological modeling framework to quantify the effects of water rights allocation on a representative semiarid river basin. Through this framework we analyze the tradeoffs of several water management practices, institutional settings, and regional policies on municipal and agricultural sectors. Generally, the agent-based adoption of water management strategies can alleviate the harm of water scarcity while providing positive feedbacks to reducing municipal costs and increasing agricultural profit from production. Household adoption of xeriscaping is considered the most important technology to lower urban demands and offset the negative externalities of rural-to-urban water transfers. Additionally, an uninhibited water market leads to the most effective allocation of water rights, providing benefits to both rural and municipal communities. The future allocation of water rights under climatic, institutional, agricultural, and technological uncertainty shows significant sensitivity to fluctuations in water conveyance infrastructure costs. Such changes in infrastructure costs (i.e. 50% to 150%) can nearly double the expected costs of reliably supplying water to urban households. However, urban water supply planners can incentivize the adoption of water management practices to stabilize these costs. Further, required water purchases for land developers set by urban planners can be used as a key policy tool for keeping costs low. This work contributes to existing literature in integrated water resources management to help understand the effects of water scarcity and provide practical solutions for urban water planners in rapidly urbanizing semiarid regions.
Keywords: economics; sustainability; water resources; optimization; agriculture; uncertainty